Pengaruh teknik proning terhadap dyspnea pada pasien penyakit paru obstruksi kronis (PPOK) - Wijaya, Dis Latif; Putra, Fajar Alam; Sutrisno (JOURNAL of Public Health Concerns, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation and chronic inflammation due to exposure to irritants such as cigarette smoke, air pollution, and industrial substances. As one of the four major non-communicable diseases, the global burden of COPD reached 213.39 million cases in 2021. In Indonesia, the prevalence was 3.7% (≈9.2 million people), with Central Java accounting for 2.1%, or 31,817 patients. Dyspnea is a key symptom requiring intensive monitoring and management. A combination of pharmacological and non-pharmacological therapies, particularly the proning technique, has been shown to effectively improve pulmonary oxygenation and ventilation. At Dr. Soehadi Prijonegoro Regional Hospital in Sragen in January 2025, all 32 COPD patients in the Sakura and Aster lung wards experienced dyspnea, with five experiencing decreased oxygen saturation despite receiving oxygenation, nebulizers, and oral and injectable medications. Purpose: To analyze the effect of the proning technique on dyspnea intensity in COPD patients. Method: A one-group pre-test and post-test pre-experimental method was used on 32 COPD patients at Soehadi Prijonegoro Hospital for one month. Dyspnea was measured using the Borg Scale and respiratory rate observations before and after non-pharmacological intervention. Analysis was performed using the Wilcoxon test. Results: The average age of respondents was 57.66 years with a standard deviation of 12.05 years, ranging from 19 to 68 years. The majority of respondents were aged ≥ 60 years (21 respondents) (65.6%), gender was predominantly male (22 respondents) (68.8%), and the majority of respondents had a junior high school education (16 respondents) (50%). The majority of respondents were farmers (15 respondents) (46.9%), family support was mostly from younger siblings (18 respondents) (56.3%), and the duration of the disease was mostly more than 1 year (20 respondents) (62.5%). While the highest level of dyspnea before the proning technique intervention was in the moderate dyspnea category, namely 21 (65.6%), while after the proning intervention the highest proportion was in the mild dyspnea category, namely 17 (53.1%). The median dyspnea score before the proning technique intervention was 4 and the median dyspnea score after the proning technique intervention was 2. Based on the Wilcoxon test, the p value was <0.001. Conclusion: The application of the prone positioning technique significantly reduced the degree of dyspnea, with a decrease in the proportion of moderate dyspnea from 65.6% to 12.5%, with a p-value <0.001. These findings demonstrate the effectiveness of prone positioning as a non-pharmacological intervention in COPD management. Suggestion: Prone positioning should be routinely integrated into COPD management protocols in primary and referral healthcare facilities. Health education interventions should focus on the elderly, farmers, and patients with low education levels to improve understanding and adherence to self-care. Healthcare providers should involve families as active participants in treatment planning and long-term monitoring. Furthermore, further research with larger sample sizes is recommended to evaluate long-term effects and patient quality of life. Keywords: Chronic Obstructive Pulmonary Disease (COPD); Dyspnea;  Proning Technique Pendahuluan: Penyakit Paru Obstruksi Kronis (PPOK) adalah gangguan pernapasan progresif yang ditandai oleh hambatan aliran udara persisten dan inflamasi kronis akibat paparan iritan seperti asap rokok, polusi udara, dan zat industri. Sebagai salah satu dari empat penyakit tidak menular utama, beban global PPOK mencapai 213.39 juta kasus pada 2021, sedangkan di Indonesia prevalensinya 3.7% (≈9.2 juta orang), dengan Jawa Tengah mencatat 2.1% atau 31,817 penderita. Dyspnea merupakan gejala kunci yang memerlukan pemantauan dan pengelolaan intensif, di mana kombinasi terapi farmakologis dan nonfarmakologis khususnya teknik proning, terbukti efektif meningkatkan oksigenasi dan ventilasi paru. Di RSUD dr. Soehadi Prijonegoro Sragen pada Januari 2025, seluruh 32 pasien PPOK di ruang paru Sakura dan Aster mengalami dyspnea, dengan lima di antaranya mengalami penurunan saturasi oksigen meski telah menerima oksigenasi, nebulizer, serta obat oral dan injeksi. Tujuan: Menganalisis pengaruh teknik proning terhadap intensitas dyspnea pada pasien PPOK. Metode: Metode pre-eksperimental one-group pre-test dan post-test digunakan pada 32 pasien PPOK di RS Soehadi Prijonegoro selama satu bulan. Dyspnea diukur dengan Skala Borg dan observasi respiratory rate sebelum dan sesudah intervensi nonfarmakologis. Analisis dilakukan menggunakan uji Wilcoxon. Hasil: Mendapatkan rata-rata usia responden adalah 57.66 tahun dengan standar deviasi 12.05 tahun dalam rentang usia 19-68 tahun dan mayoritas responden berusia ≥ 60 tahun sebanyak 21 responden (65.6%), jenis kelamin responden mayoritas adalah laki-laki sebanyak 22 responden (68.8%), dan tingkat pendidikan mayoritas adalah SMP sebanyak 16 responden (50%), sebagian besar status pekerjaan responden adalah petani sebanyak 15 responden (46.9%), dukungan keluarga paling banyak adik/ kakak sebanyak 18 responden (56.3%), durasi penyakit paling banyak lebih dari 1 tahun sebanyak 20 responden (62.5%). Sedangkan tingkat dyspnea terbanyak sebelum intervensi teknik proning adalah kategori dyspnea sedang yaitu sebanyak 21 (65.6%), sedangkan setelah intervensi proning proporsi terbanyak pada kategori dyspnea ringan yaitu sebanyak 17 (53.1%). Median skor dyspnea sebelum intervensi teknik proning adalah  4 dan median skor dyspnea setelah intervensi teknik proning adalah  2 . Berdasarkan uji Wilcoxon mendapatkan nilai  p < 0.001.  Simpulan: Penerapan teknik prone positioning secara signifikan menurunkan derajat dyspnea, dengan penurunan proporsi dyspnea sedang dari 65.6% menjadi 12.5%, dan p Value < 0.001. Temuan ini menunjukkan efektivitas proning sebagai intervensi nonfarmakologis dalam manajemen PPOK. Saran: Sebaiknya teknik prone positioning diintegrasikan secara rutin dalam protokol penanganan PPOK di fasilitas kesehatan primer dan rujukan. Intervensi edukasi kesehatan perlu difokuskan pada lansia, petani, dan pasien berpendidikan rendah untuk meningkatkan pemahaman dan ketaatan pada perawatan diri. Penyedia layanan kesehatan harus melibatkan keluarga sebagai bagian aktif dalam rencana pengobatan dan pemantauan jangka panjang. Selain itu, penelitian lanjutan dengan sampel lebih besar dianjurkan untuk mengevaluasi efek jangka panjang dan kualitas hidup pasien.